PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA MENGGUNAKAN METODE EKSPERIMEN DI KELAS IV SD - Finarosa, Dwi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the fact that the school students in the learning process less active and interested in the subject, thus causing low student learning outcomes. This is due to lack of teachers in the learning process using the steps appropriate approach in the learning process, the teacher is more dominant and less conventional methods using a variety of methods, less teacher worksheets given in accordance with the material being taught. This can be overcome by using experiment methods. The purpose of this study was to describe an increase in student learning outcomes in learning science by using the experiment method in class IV Elementary School 38 Kuranji Padang. This study used qualitative and quantitative approaches to classroom action research. The subjects were elementary school fourth grade students 38 Kuranji Padang, the class teacher as an observer, and researcher as teacher practitioners. In practice, the study was conducted in two cycles. Each cycle consists of planning, implementation, observation and reflection. The results of research on learning plan cycle I is 66% and in the second cycle increased by an average of 84%. Implementation of the activities teachers learning cycle I is 67.5% and in the second cycle increased is 87.5%. In the student activity cycle I get an average of 62.5% and an increase in cycle II is 85%. Furthermore, student learning outcomes in all three aspects of the cycle I is 65.40 with a qualifying (C) and the second cycle of student learning outcomes in all three aspects of increasing is 75.10 with a qualifying (B). Experiment method can improve learning outcomes of students in the learning of  IPA in elementary school.